Advancing Public Ocean Perceptions Research: a guiding approach to strengthen collaboration for ocean health - Jen McRuer; Diz L. Glithero (FACETS)
The United Nations Decade of Ocean Science for Sustainable Development (2021–2030) emphasizes advancing our understanding of the ocean and promoting sustainable practices to ensure ocean health and interconnected well-being. As we approach the halfway mark, achieving this agenda requires informed and actionable collaboration among professionals involved in ocean science, management, conservation, industry, communication and education, as well as interested and/or affected groups, guided by science–policy–society linkages. Prioritizing the role of society can help to motivate and enable the restoration of people–ocean relationships. Understanding public ocean perceptions is crucial for grounding such efforts in place-based relevance. This paper discusses the role of Public Ocean Perceptions Research (POPR), a form of ocean literacy research, in this context. We analyse five pan-Canadian POPR surveys, each with specific ocean-focused objectives, to highlight their potential to contribute to ocean–human health. The surveys consistently reflect some themes (e.g., attitudes and behaviours), while lacking others (e.g., ocean solutions). Particular attention on where a marine social science lens is, or may be reflected, can help to inform the design and analysis of future POPR studies to better understand how people understand, value, and care for the ocean. We position how arising themes and ocean literacy dimensions can be used in ongoing research efforts, to inform marine conservation and broader ocean science policy.